Tin Intercalated Ultrathin MoO3 Nanoribbons for Advanced Lithium–Sulfur Batteries. Issue 7 (27th December 2018) - Yang, Weiwei; Xiao, Jiewen; Ma, Yang; Cui, Shiqiang; Zhang, Peng; Zhai, Pengbo; Meng, Lingjia; Wang, Xingguo; Wei, Yi; Du, Zhiguo; Li, Bixuan; Sun, Zhibo; et al.
Abstract: Heteroatom doping strategies have been widely developed to engineer the conductivity and polarity of 2D materials to improve their performance as the host for sulfur cathode in lithium–sulfur batteries. However, further improvement is limited by the inhomogeneity and the small amount of the doping atoms. An intercalation method to improve the conductivity and polarity of 2D‐layered α‐MoO3 nanoribbons is developed here, thus, resulting in much improved electrochemical performance as sulfur host with better rate and cycle performance. The first principle calculations show that the binding energy of MoO3 and lithium polysulfides, lithium sulfide and sulfur is significantly improved after Sn intercalation. The Sn0.063 MoO3 ‐S cathode delivers an initial specific capacity of 1390.3 mAh g −1 at 0.1 C with the Coulombic efficiency up to 99.7% and shows 79.6% retention of the initial capacity over 500 cycles at 1 C rate with a capacity decay of 0.04% per cycle. This intercalation method provides a new strategy to engineer the electrochemical properties of 2D materials. Abstract : The intercalation method is developed to tune the electrochemical properties of 2D materials. Sn atoms intercalated within ultrathin α‐MoO3 nanoribbons present improved conductivity and enhanced binding energy with lithium polysulfides, lithium sulfide and sulfur, which is confirmed by both experimental and theoretical data and results in much improved electrochemical performance as sulfur host with better rate and cycle performance.